User Experience on Satisfaction and Willingness to Pay for Video Streaming Services in Thailand - Wichitsathian, Sareeya (Journal of Posthumanism, 2025)
This study provides insight into the opinions of people in Thailand who have experience using video streaming services, classified as Generations X, Y, and Z. It examined user experience, the quality of e-subscription services, perceived value, satisfaction, and willingness to pay for video streaming services. The findings indicate that the structural equation model developed in this research aligns with empirical data derived from theories, concepts, and relevant studies. The study reveals that user experience significantly impacts satisfaction, quality of e-subscription service, and perceived value in video streaming services. Meanwhile, the quality of e-subscription services influences both satisfaction and willingness to pay. While perceived value affects satisfaction, it does not directly affect willingness to pay. However, satisfaction has a direct effect on willingness to pay. These key findings provide video streaming business operators with valuable data for improving their services to meet user demands, enhance satisfaction, and increase willingness to pay. Specifically, businesses should focus on fostering user satisfaction while proactively addressing potential dissatisfaction, as negative experiences could impact users’ willingness to pay.